The influence of monosodium glutamate on the development of oxidative-nitrosative stress in the large cerebral hemispheres of rats under the combination of a change in the “light-dark” cycle and a systemic inflammatory response - O. A. Volkova; O. Ye. Akimov; V. O. Kostenko (Сучасні медичні технології)
Today, the issue of the consequences of disrupting the normal “light-dark” cycle is becoming increasingly important, and the link between the development of a systemic inflammatory response (SIR) and circadian rhythm disorders has been confirmed. The effect of monosodium glutamate on the human body is being actively studied.